Not a solo ride: co-constructed peer mentoring for early-career educational leadership faculty. Issue 4 (21st November 2019) - Morton, Benterah C.; Gil, Elizabeth
Abstract : Purpose: The purpose of this paper is to describe the origins of a co-constructed peer-mentoring model designed by and for early-career faculty representing historically underrepresented groups in the field of educational leadership. The model, which includes components of the multicultural feminist model of mentoring, pays specific attention to early-career faculty development and well-being and outlines the need for and benefits of peer-mentoring programs. Design/methodology/approach: This qualitative study details the experiences of the development and implementation of a peer-mentoring program based on a review of literature that points out the need to provide mentoring opportunities for early-career educational leadership faculty, from historically underrepresented populations, and further posits peer-mentoring as an avenue to enhance faculty development and well-being. Findings: Faculty representing historically underrepresented groups often experience challenges related to their identities, alongside the general pressures of working toward tenure. Peer-mentoring groups provide support with which to navigate these challenges. Peer-mentor groups are a supplement to other professional groups and interactions within departments and institutions. Practical implications: The model has implications of being able to prepare institutional leaders to work toward institutionalizing mentoring programs that take into consideration invisible labor while promoting professional growth and personal wellness, thereby increasing the satisfaction and retention of faculty. Originality/value: This peer-mentoring model can be used as a tool to leverage collective support, rather than emphasize individual success. As a support vehicle, it can foster a cultural change within the field of educational leadership that supports collaboration over competition.